2016
DOI: 10.3389/fevo.2016.00107
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Circulating Testosterone during Mating Predicts Reproductive Success in a Wild Songbird

Abstract: Testosterone is an important sex hormone and mediates reproduction in male vertebrates. There is ample evidence that testosterone coordinates the expression of physiological, morphological, and behavioral traits during reproduction and many of these traits are under sexual selection. However, only few studies so far have examined if individual variation in testosterone is correlated with reproductive success. Because socially monogamous bird species pass through different phases within a breeding cycle and eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Blood testosterone level is an important indicator of fertility and reproductive activity (Apfelbeck et al, 2016 ; Preston et al, 2012 ). This steroid hormone promotes sexual behavior and cognitions in order to facilitate mate acquisition or mating directly (Roney et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood testosterone level is an important indicator of fertility and reproductive activity (Apfelbeck et al, 2016 ; Preston et al, 2012 ). This steroid hormone promotes sexual behavior and cognitions in order to facilitate mate acquisition or mating directly (Roney et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood testosterone level is an important indicator of fertility and reproductive activity (Apfelbeck et al, 2016;Preston et al, 2012).…”
Section: F I G U R E 1 Effect Of Incorporating Artemisia Herba Alba Andmentioning
confidence: 99%
“…For example, in an experimental study in dark-eyed juncos (Junco hyemalis) , testosterone treated males suffered fewer losses of paternity than control males [97]. Supporting the fitness relevance of testosterone during mating, earlier studies in European stonechats found that variation in testosterone concentrations during mating, but not during parental stages, was associated with reproductive success in temperate stonechats [72]. Similar to stonechats, testosterone concentrations also peaked during nest-building and mate guarding in temperate barn swallows (Hirundo rustica, [20]), blue tits ( Cyanistes caeruleus, [16]) and in tropical Seychelle warblers (Acrocephalus sechellensis, [98]).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, we randomly assigned two decoys from Austria and in East Africa eight decoys from each of the two populations, Kinangop (Kenya) and Arusha (Tanzania). In stonechats, stimulation with a decoy and playback does not change circulating testosterone concentrations [ 72 ], and hence to analyze testosterone profiles data from passively and actively caught birds were combined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation